Strontium titanate films prepared by spray pyrolysis - Brankovic, G.; Brankovic, Z.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2004)
Strontium titanate thin films were prepared by spray pyrolysis technique. Deposition parameters, such as solution concentration, time and temperature of deposition, and flow rate of carrier gas were optimized to obtain dense films without cracks. Films with different thicknesses were prepared through the control of deposition time. Prepared thin films were homogeneous, well crystallized, with uniform grain size. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: films; sol-gel processes; strontium titanate